Stimulant Treatment of Young People in the United States - Olfson, Mark (J Child Adolesc Psychopharmacol, 2016)
Objective: To describe national stimulant treatment patterns among young people focusing on patient age and prescribing specialty. Methods: Stimulant prescriptions to patients aged 3–24 were analyzed from the 2008 IMS LifeLink LRx Longitudinal Prescription database (n = 3,147,352), which includes 60% of all U.S. retail pharmacies. A subset of young people from 2009 with service claims (n = 197,654) were also analyzed. Denominators were adjusted to generalize estimates to the U.S. population. Population percentages filling ≥1 stimulant prescription during the study year by sex and age group (younger children, 3–5 years; older children, 6–12 years; adolescents, 13–18 years; and young adults, 19–24 years) were determined. Percentages prescribed stimulants by psychiatrists, child and adolescent psychiatrists, pediatricians, and other physicians were also determined along with percentages that were treated for a long or short duration; coprescribed other psychotropic medications; used psychosocial services; and received clinical psychiatric diagnoses. Results: Population percentages with any stimulant use varied across younger children (0.4%), older children (4.5%), adolescents (4.0%), and young adults (1.7%). Among children and adolescents, males were over twice as likely as females to receive stimulants. Percentages of stimulant-treated young people with ≥1 stimulant prescription from a child and adolescent psychiatrist varied from younger children (19.1%), older children (17.1%), and adolescents (18.2%) to young adults (10.1%), and these percentages increased among those who were also prescribed other psychotropic medications: young children (31.0%), older children (37.9%), adolescents (35.1%), and young adults (15.8%). Antipsychotics were the most commonly coprescribed class to stimulant-treated younger (15.0%) and older children (11.8%), while antidepressants were most commonly coprescribed to adolescents (17.5%) and young adults (23.9%). Conclusions: Stimulant treatment peaks during middle childhood, especially for boys. For young people treated with stimulants, including younger children, low rates of treatment by child and adolescent psychiatrists highlight difficulties with access to specialty mental health services.